Kesalahan Ejaan dan Tanda Baca pada Berita Online Terbitan Sukoharjonews Edisi Oktober 2024 - Feby Rani Sokawati; Duwi Rahayu Ningsih; Sri Muryati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
As a communication tool, language requires precise rules in spelling and punctuation to convey messages effectively. Speaking means the activity of using a language. Language errors often occur due to language users who do not understand the language rules they use. This study was made with the aim of identifying and analyzing spelling and punctuation errors contained in online news published by Sukoharjonews in the October 2024 edition. This research uses a descriptive qualitative method to collect and analyze data containing language errors. This analysis classifies the types of errors contained in the online news portal into two types of categories, namely the spelling error category and the punctuation error category. The results of the analysis show the existence of various errors such as errors in writing foreign language absorption words that are not italicized which is the most common form of error found, as well as errors in the use of punctuation marks which often experience errors in placing a certain punctuation mark. These errors can potentially damage the clarity of the message and reduce readers' trust in the news. Therefore, news writers need to pay more attention to spelling and punctuation rules to ensure effective and accurate communication. This research emphasizes the importance of a deep understanding of spelling and punctuation as part of the writing skills that journalists and writers should possess.